Corporate Social Responsibility (CSR) : Insights From A Systematic Literature Review - Tyas Prasetyawati; Gusti Syavinatusshara Al Habib; Mukhtaruddin, Mukhtaruddin (International Journal of Education, Vocational and Social Science, 2024)
This systematic literature review focuses on recent studies on Corporate Social Responsibility (CSR), specifically from 2020 to 2024. The review aims to provide a comprehensive understanding of CSR developments, current trends, and theoretical foundations, with particular attention to recent academic contributions ( United Nations Global Compact, 2022). This study examines the role of CSR in promoting sustainability across environmental, social, and economic dimensions, analyzes the impact of CSR activities on stakeholders, and identifies research gaps for future exploration. It also discusses the theoretical frameworks commonly used in CSR studies and explores the methodologies used by researchers. (Carroll, AB, & Brown, J, 2022). This study uses a Systematic Literature Review (SLR), which systematically collects, evaluates, and analyzes relevant literature on Corporate Social Responsibility (CSR) to uncover research trends and gaps. One of the important findings is the relationship between CSR and financial performance, which has received considerable attention in recent literature. Many studies highlight a positive correlation, indicating that well-implemented CSR initiatives can enhance brand reputation, customer loyalty, and overall profitability.